The Role of Muhammadiyah in Realizing Divine and Human Values: Peran Muhammadiyah dalam Mewujudkan Nilai Ketuhanan dan Kemanusiaan - Haryanto, Sigit; Fatmawati, Rini; Mujazin, M (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
The role of Muhammadiyah in building the nation needs to be explored and disseminated through scientific channels. This is so that what Muhammadiyah does is not underestimated. This study aims to explore electronically exactly the role of Muhammadiyah in implementing the values of Pancasila. Data is collected by searching the internet related to Muhammadiyah's activities in implementing the values of Pancasila from the first and second precepts. Next, the data is analyzed with qualitative data analysis techniques proposed by Spradley. The results of the analysis are as follows: Muhammadiyah correctly implements the values of Pancasila, first precept and second precept. Implementation is reflected in the activities carried out by Muhammadiyah residents at both the central and regional levels. Types of activities are scattered in the container of divine activities. Finally, it can be concluded that Muhammadiyah plays an active role in implementing the values of Pancasila and always supports the government's efforts to realize harmony and welfare of the Indonesian people.